Effective Remediation of Lead Ions from Aqueous Solution by Chemically Carbonized Rubber Wood Sawdust: Equilibrium, Kinetics, and Thermodynamic Study - Swarup Biswas; Umesh Mishra (Journal of Chemistry)
Rubber wood sawdust was carbonized into charcoal by chemical treatment which was used for removal of lead ion from aqueous solution. The work involves batch experiments to investigate the pH effect, initial concentration of adsorbate, contact time, and adsorbent dose. Experimental data confirmed that the adsorption capacities increased with increasing inlet concentration and bed height and decreased with increasing flow rate. Adsorption results showed a maximum adsorption capacity of 37 mg/g at 308 K. Langmuir, Freundlich, and Temkin model adsorption isotherm models were applied to analyze the process where Temkin was found as a best fitted model for present study. Simultaneously kinetics of adsorption like pseudo-first-order, pseudo-second-order, and intraparticle diffusion models were investigated. Thermodynamic parameters were used to analyze the adsorption experiment. Fourier transform infrared spectroscopy, scanning electron microscope, and energy dispersive X-ray spectroscopy confirmed the batch adsorption of lead ion onto chemically carbonized rubber wood sawdust.